Impact of Human Umbilical Cord Blood Mononuclear Cells on Gentamicin-Induced Renal Injury and Genotoxicity in Rats - Abu Almaaty, Ali H.; Elmasry, Reham A.; Farrag, Mayada S.; Althobaiti, Fayez; Aldhahrani, Adil; Fayad, Eman; Hussain, Mona A. (Frontiers in Medicine, 2021)
(1) Background: Acute kidney injury (AKI) is described as a sudden decline in renal function. AKI has become more popular in recent years. Gentamicin (GM) is an antibiotic its prolonged use leads to (AKI) that accompanied by high death rate; (2) Methods: 50 adult female albino rats weighing 150-200 g were used. The animals were divided into five groups: 1st normal healthy control group, 2nd group received only 1× 106 HUCB Stem Cells(SCs) /rat by intravenous (iv) injection, 3rd diseaded group was given GM 100 mg/kg for 10 consecutive days by intraperitoneal injections, 4th preventive group received 1×106 HUCB SCs /rat by iv injection 24 hours before gentamicin treatment, and 5th treated group received 1× 106 HUCB SCs /rat by iv injection 24 hours after gentamicin treatment. After one week of treatment, blood samples were collected and kidneys were removed for histopathological examination; (3) Results: Rats treated with human umbilical cord blood mononuclear cells in the treated group has significant decrease in percentage of renal damage, low levels of biomarkers for nephrotoxicity, serum creatinine and blood urea nitrogen and low chromosomal aberrations compared to diseased 3rd group. Gene expression of KIM-1 and NGAL were down regulated in treatment with HUCB; (4) Conclusions: HUCB SCs have a curative effect against AKI and genotoxicity induced by gentamicin owing to its regenerative property.